Resilient coastal cities for enhancing tourism economy: Integrated planning approaches - Sonia Chand Sandhu; Vedanti Kelkar; Vaideeswaran Sankaran (Asian Development Bank Institute (ADBI), 2019)
The objective of this paper is to recommend planning options for improving the resilience, competitiveness, and sustainability of coastal cities. Insights for an improved understanding of dynamic coastal ecosystems and tourism impacts are shared. These are based on project level solutions and experiential knowledge of practices and a literature review of impacts of (a) growing pressures from coastal tourism in cities, (b) urban and environmental management practices, and (c) prevailing processes for creating and managing coastal infrastructure. Solutions to the identified problems are based on an analysis of the coastal ecosystems across three broad pillars: (i) city management, (ii) pollution and climate change risks, and (iii) coastal tourism. The problems range from a fragmented approach to coastal infrastructure planning; land and water pollution, fragmentation of natural ecosystems' loss of habitat and unique biodiversity, salinity intrusion, and climate change risks from sea level rises and natural disasters; and tourism economy dependencies on the management of natural assets and cross-sectoral planning. The paper recommends paradigm shifts for innovative planning and policy approaches that engage communities, institutions, and other stakeholders.
Keywords: Q54; Q56; Q57; Q58; Z32; R11; R14; 330; coastal infrastructure and ecosystems; natural assets; planning; resilience policy; tourism; economy; competitiveness; communities; institutions; pollution; climate change; systems thinking; nature-based solutions; evidence-based approach